Special low-gloss and low-reflectivity coating for aluminum coil and preparation method of special low-gloss and low-reflectivity coating
By forming a low-gloss, low-reflectivity coating on the surface of aluminum coils, the problem of high reflectivity in existing aluminum coil coatings is solved, achieving low gloss and high matte finish on the aluminum coil surface, and enhancing the uniformity and physical properties of the coating.
Patent Information
- Application Number
- CN202511117744.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-11
- Publication Date
- 2025-11-07
AI Technical Summary
Existing aluminum coil coatings cannot effectively reduce reflectivity, which affects their application in high-end applications.
A low-gloss, low-reflectivity coating is formed by using components such as polyurethane acrylate dispersion, matting agent, titanium dioxide and carbon black composite supported on silicon titanium oxide, and mica powder composite supported on silica, and then curing it with ultraviolet light.
It achieves low gloss and low reflectivity on the surface of aluminum coils, improves matte finish and coating uniformity, and enhances the coating's layering and physical properties.
Smart Images

Figure BDA0005541945970000081
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of aluminum coil surface treatment, in particular to a low-gloss and low-reflectivity coating special for aluminum coil and a preparation method thereof. BACKGROUND
[0002] The aluminum coil is a metal product processed by a casting and rolling machine through calendering and bending, and is widely used in the fields of electronics, packaging, construction and machinery. According to different metal elements contained in the aluminum coil, the aluminum coil can be roughly divided into nine categories, namely 1000 series, 2000 series aluminum plate, 3000 series aluminum plate, 4000 series aluminum plate, 5000 series, 6000 series, 7000 series, 8000 series and 9000 series.
[0003] With the rapid development of the aviation industry, the research and application of airport building materials have also attracted widespread attention. Traditional airport building materials often focus on their durability, fire resistance and safety, while ignoring the optical properties and visual effects of the materials. The research and application of diffuse reflection materials have become a major trend in the field of airport construction.
[0004] The surface coating of the existing ordinary coating aluminum used for decoration has a certain direct reflection of illumination light, that is, the commonly known reflection. The reflection will cause irritation to the human visual organs, that is, the commonly known glare, thereby in order to reduce the reflectivity, the surface of the coating aluminum is generally sprayed with a coating to reduce the influence of reflection on people.
[0005] The lowest gloss of the general ordinary white coating is 10%, and the diffuse reflectivity is generally about 70%. The high-end places such as airports, high-speed rails and office buildings have higher requirements for the reflection of the coating, thereby the general white coating aluminum is not suitable for high-end places, so the super-low-gloss diffuse reflection coating product with higher whiteness, lower direct reflectivity and higher diffuse reflectivity is more popular in the specific market.
[0006] Patent No. CN104449200A discloses a kind of heat insulation powder coating and its preparation method, coating method, coating and the application of the heat insulation powder coating, the component (weight parts) of the heat insulation powder coating includes: film forming agent 90-100, curing agent 1-10, foaming agent 0.1-2 and leveling agent 0.5-5;The ordinary aluminum alloy profile and aluminum alloy door and window of the heat insulation coating of the application need not be inserted between the two aluminum materials Non-metallic material, and can reduce the complexity of coating process, ensure the heat preservation performance.But the above prior art still has the following problems: although through the setting of foaming agent and the like structure, only need to be sprayed on the metal substrate during coating process, and curing is carried out at a temperature higher than the decomposition temperature of foaming agent, although the coating process is simplified and the complexity of coating process is reduced, but the reflectivity of the coating cannot be reduced, which may result in high reflectivity of the coating, affecting the subsequent use.
[0007] Therefore, a low-gloss, low-reflectivity coating special for aluminum coil is proposed to produce the above-mentioned coated aluminum and solve the above-mentioned problems. SUMMARY
[0008] To solve the above technical problems, a low-gloss, low-reflectivity coating special for aluminum coil and its preparation method are provided. The coating has good rheological properties, which facilitates uniform roll coating on the surface of the aluminum coil. The coating formed on the surface of the aluminum coil has good layering, and the gloss and reflectivity are both low.
[0009] To achieve the above purposes, the present application realizes the following technical solutions:
[0010] A low-gloss, low-reflectivity coating special for aluminum coil includes the following components by weight:
[0011] Polyurethane acrylate dispersion 60-90 parts, photoinitiator 2-5 parts, pigment and filler 20-30 parts, auxiliary agent 6-10 parts, solvent 18-35 parts;
[0012] The polyurethane acrylate dispersion is prepared by the following method:
[0013] (1) Under nitrogen protection, toluene diisocyanate and methyl acrylate are added to the reactor and mixed uniformly, and reacted at 70-80℃ for 2-3h;
[0014] (2) Add carboxyl type chain extender and maintain the reaction temperature of step (1) for 1-3h chain extension reaction;
[0015] (3) Then cool to 55-65℃, add polymerization inhibitor and catalyst and react for 3-5h;
[0016] (4) then add the basic amine substance (such as triethylamine) to adjust the pH value to 7-9, to obtain the polyurethane acrylate prepolymer, and emulsify to obtain the polyurethane acrylate dispersion;
[0017] The color filler is selected from one or more combinations of matting agent, titanium dioxide supported on silicon-titanium oxide and / or carbon black composite, and silica supported mica powder composite.
[0018] Further, in step (1), the molar ratio of the hydroxypropyl methacrylate and the toluene diisocyanate is 1:0.8-1.2;
[0019] In step (2), the carboxyl type chain extender is one or more than two kinds of mixture of dimethylol propanoic acid and dimethylol butanoic acid, and the mass ratio of the carboxyl type chain extender to the toluene diisocyanate is 0.6-1:1;
[0020] In step (3), the polymerization inhibitor is p-hydroxyanisole, and the catalyst is dibutyltin dilaurate, and the molar ratio of the polymerization inhibitor, the catalyst, the hydroxypropyl methacrylate and the toluene diisocyanate is 0.001-0.1:0.075-0.2:1-1.2:0.9-1.1;
[0021] In step (4), the emulsification process is: adding an emulsifier to the polyurethane acrylate prepolymer, stirring at a speed of 800-1000 rpm for 0.5-2 h, adding ethanol in multiple batches, and uniformly dispersing to obtain the product.
[0022] The emulsifier is selected from any one of TX-10 and T-80; and the mass ratio of the emulsifier, the polyurethane acrylate prepolymer and ethanol is 5-10:85-100:70-110.
[0023] Further, the color filler is selected from a combination of the three of the matting agent, titanium dioxide supported on silicon-titanium oxide and / or carbon black composite, and silica supported mica powder composite, and the addition amount of the matting agent, titanium dioxide supported on silicon-titanium oxide and / or carbon black composite, and silica supported mica powder composite is 8-10:35-50:45-50 by weight.
[0024] The matting agent is selected from fumed silica with a specific surface area of 350-410 m 2 / g and a particle size of 200-500 mesh; and the titanium dioxide in the titanium dioxide supported on silicon-titanium oxide and / or carbon black composite is rutile titanium dioxide with a particle size of 10-50 nm, and the carbon black has a particle size of 100-200 nm.
[0025] Furthermore, the method for obtaining the composite of titanium dioxide and / or carbon black supported by silicon titanium oxide is as follows: tetrabutyl titanate and tetraethyl orthosilicate are added to a dispersion containing titanium dioxide and / or carbon black, the pH of the reaction system is adjusted to acidic and the reaction is carried out. After the reaction is completed, the reaction solution is washed repeatedly with anhydrous ethanol, the product is separated and dried in a vacuum oven at a temperature below 50°C, and finally calcined to obtain the composite of titanium dioxide and / or carbon black supported by silicon titanium oxide.
[0026] The pH value is 2-5, the reaction temperature is 30-70℃, the reaction time is 0.5-24h, the calcination temperature is 400-600℃, and the calcination time is 3-8h.
[0027] When selecting titanium dioxide or carbon black, the weight ratio of titanium dioxide or carbon black, tetrabutyl titanate, and tetraethyl orthosilicate is 1:0.03-0.05:0.15-0.35.
[0028] When selecting a combination of titanium dioxide and carbon black, the weight ratio of titanium dioxide to carbon black is 1:0.2, and the total weight ratio of titanium dioxide and carbon black to tetrabutyl titanate and tetraethyl orthosilicate is 1.2:0.032-0.06:0.18-0.45.
[0029] Furthermore, the method for obtaining the silica-supported mica powder composite is as follows: silica powder with a particle size of 1-100 nm and mica powder with a flake size of 1-250 nm are ball-milled and mixed under the action of a silane coupling agent to obtain the silica-supported mica powder composite; wherein the mass ratio of the silica powder, the mica powder, and the silane coupling agent is 1:0.5-1:0.1-0.3; the ball milling uses zirconia beads with a particle size of 0.6-1 mm as the grinding medium to continuously grind the material for 1-3 hours. A conventional modified silica coupling agent, such as KH570, can be selected as the silane coupling agent.
[0030] Furthermore, the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone;
[0031] The solvent is a mixture of xylene and butyl acetate in a weight ratio of 10:45-60;
[0032] The additive is selected from one or more of leveling agents, dispersants, and defoamers;
[0033] The leveling agent is an organosilicon leveling agent, and the leveling agent is added to the coating components in the amount of 0.5-2 parts by weight.
[0034] The dispersant is a sodium polycarboxylate dispersant, and the dispersant is added to the coating components in the amount of 1-3 parts by weight.
[0035] The defoaming agent is a polyether modified silicone defoaming agent, and the defoaming agent is added in the coating component in a weight fraction of 3-5 parts.
[0036] The preparation method of the low-gloss and low-reflectivity coating special for the aluminum coil comprises the following steps:
[0037] The coating components are added into a stirring tank in proportion, and stirring is continuously carried out at a stirring speed of 1000 rpm or more for 0.5-2 h, so that the low-gloss and low-reflectivity coating special for the aluminum coil is prepared.
[0038] Further, the low-gloss and low-reflectivity coating is coated on the surface of the aluminum coil product, and a film is formed after ultraviolet light curing, the film thickness is 2-5 microns, the light curing channel length is 50 m, and the coating speed is 50-80 m / min.
[0039] Beneficial technical effects:
[0040] The self-made polyurethane acrylate dispersion containing double bonds is adopted, triethylamine is used as a neutralizing agent of the carboxylic acid type water-based resin, and the ability of the triethylamine to initiate active radical polymerization under ultraviolet light is utilized, so that the prepared coating is easy to cure, and the film curing speed is fast.
[0041] After the coating is cured, small protrusions are formed on the surface, so that when light is irradiated on the aluminum coil with the coating, the light is diffusely reflected, thereby reducing the gloss of the aluminum coil and improving the matte degree of the aluminum coil.
[0042] The silica loaded pigment filler composite is adopted, the silica loaded titanium dioxide powder, carbon black powder composite and silica loaded mica powder composite are added into the coating, the whiteness of the coating is improved, and the rheological property of the coating is adjusted. DETAILED DESCRIPTION
[0043] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments of the present application. The description of the at least one example embodiment is actually only illustrative in nature and by no means as any limitation to the present application and its application or use. Based on the embodiments in the present application, all other embodiments obtained by a person of ordinary skill in the art without creative effort fall within the scope of protection of the present application.
[0044] Unless specifically stated otherwise, the numerical values stated in these embodiments do not limit the scope of the present application. The techniques and methods known to those of ordinary skill in the relevant art can not be discussed in detail, but should be considered as part of the specification where appropriate. In all examples shown and discussed here, any specific value should be interpreted as merely exemplary, not as a limitation. Therefore, other examples of the example embodiments can have different values.
[0045] The experimental methods in the following embodiments not specified in the specific conditions are generally determined according to the national standard; if there is no corresponding national standard, it is carried out according to the general standard requirement or general method.
[0046] Preparation Example 1
[0047] This example is the preparation of a composite of silicon-titanium oxide loaded titanium white and carbon black, the specific steps are as follows:
[0048] 10 g of titanium white (rutile type titanium dioxide, particle size of 10-50 nm) and 2 g of carbon black (particle size of 100-200 nm) were dispersed in 50 mL of ethanol-water solution (volume ratio of anhydrous ethanol and water was 2:3), under continuous stirring, 0.4 g of butyl titanate and 4 g of tetraethyl orthosilicate were added, sulfuric acid was used to adjust the pH of the system to 2.5-3.5, and the hydrolysis was carried out at 56°C for 20 h. The product was filtered out, the reaction solution was washed with anhydrous ethanol several times, centrifuged, and dried in a vacuum oven at 30°C for 12 h. Finally, it was calcined at 550°C for 6 h to obtain a composite of silicon-titanium oxide loaded titanium white and carbon black.
[0049] Preparation Example 2
[0050] This example is the preparation of a composite of silicon-titanium oxide loaded carbon black, the specific steps are as follows:
[0051] 10g of carbon black (particle size 100-200nm) was dispersed in 50mL of ethanol-water solution (volume ratio of anhydrous ethanol to water 2:3). 0.3g of tetrabutyl titanate and 2g of tetraethyl orthosilicate were added under continuous stirring. The pH of the system was adjusted to 3-4 with sulfuric acid. Hydrolysis was carried out at 55℃ for 24h. The product was filtered off. After the reaction was complete, the reaction solution was washed repeatedly with anhydrous ethanol, centrifuged, and dried in a vacuum oven at 30℃ for 12h. Finally, it was calcined at 500℃ for 8h to obtain a composite of silicon titanium oxide supported on carbon black.
[0052] Preparation Example 3
[0053] This case study describes the preparation of a silica-supported mica powder composite. The specific steps are as follows:
[0054] 10g of silica powder (particle size 1-100nm), 8g of mica powder (particle size 25-250nm), and 2g of KH570 silane coupling agent were placed in a ball mill and mixed. The material was continuously ball-milled for 5 hours using zirconia beads with a particle size of 0.6-1mm as the grinding medium. During the ball milling process, the mica powder was attached to the surface of silica through the silane coupling agent to obtain a silica-supported mica powder composite.
[0055] Example 1
[0056] A low-gloss, low-reflectivity coating specifically for aluminum coils comprises the following components in parts by weight:
[0057] The composition includes 80 parts of polyurethane acrylate dispersion, 4 parts of photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone, 30 parts of pigments and fillers, 10 parts of additives, and 26 parts of solvent.
[0058] The polyurethane acrylate dispersion was prepared by the following method:
[0059] (1) Under nitrogen protection, 174.15g of toluene diisocyanate and 144.17g of hydroxypropyl methacrylate were added to the reactor and mixed evenly. The mixture was reacted at 75°C for 3 hours.
[0060] (2) Add 134.13g of carboxyl-type chain extender dimethylolpropionic acid to extend the chain, and maintain the temperature for 3h.
[0061] (3) Then add 6.21g of polymerization inhibitor p-hydroxyanisole and 50.52g of catalyst dibutyltin dilaurate. React at 55°C for 5 hours. Adjust the pH value to 7-9 by adding triethylamine, an alkaline amine, to obtain polyurethane acrylate prepolymer.
[0062] (4) 100 g of polyurethane acrylate prepolymer, 10 g of emulsifier TX-10, stirring at 1000 rpm for 2 h, adding 100 mL of ethanol in batches for multiple times, uniformly dispersing, and obtaining a polyurethane acrylate dispersion.
[0063] The color filler is a composite of silicon-titanium oxide loaded titanium dioxide and carbon black prepared in Preparation Example 1, a composite of silicon dioxide loaded mica powder prepared in Preparation Example 3, and an optical matting agent fumed silica, in a mass ratio of 40:45:10; the optical matting agent can form tiny protrusions on the surface of the cured coating, causing light to be diffusely reflected, thereby reducing the gloss of the coating and improving the matte degree of the coating.
[0064] The solvent is xylene and butyl acetate in a mass ratio of 10:55.
[0065] The auxiliary agent is 3 parts by weight of dispersant 3, 5 parts by weight of defoaming agent, and 26 parts by weight of leveling agent; the dispersant is a sodium salt of polycarboxylic acid, which can make the color filler more uniformly dispersed in the coating, adhere to the surface of the color filler, reduce the surface tension of the color filler, and prevent the color filler from agglomerating and affecting the performance of the coating; the leveling agent is an organic silicon leveling agent; and the defoaming agent is a polyether-modified organic silicon defoaming agent.
[0066] The specific preparation process of the low-gloss and low-reflectivity coating special for aluminum coils is as follows:
[0067] The above coating components are added into a stirring tank in proportion, and stirred at a stirring speed of 1000 rpm or more for 1.5 h, to obtain a low-gloss and low-reflectivity coating special for aluminum coils.
[0068] The prepared coating is coated on the surface of an aluminum coil product, and a film with a thickness of 2-5 μm is formed after ultraviolet light curing; the light curing channel length of the coated aluminum coil is 50 m, and the coating speed is 80 m / min.
[0069] Example 2
[0070] A low-gloss and low-reflectivity coating special for aluminum coils, comprising the following components in parts by weight:
[0071] 60 parts of polyurethane acrylate dispersion, 2.5 parts of photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone, 25 parts of color filler, 8 parts of auxiliary agent, and 30 parts of solvent.
[0072] The polyurethane acrylate dispersion is the same as in Example 1.
[0073] The color filler is a composite of silicon-titanium oxide loaded carbon black prepared in Preparation Example 2, and an optical matting agent fumed silica, in a mass ratio of 48:8.
[0074] The solvent is xylene and butyl acetate, and the mass ratio of the two is 10:45.
[0075] The auxiliary agent is dispersant 1.5 parts by weight, defoaming agent 3 parts by weight, and leveling agent 0.8 parts by weight; the dispersant is sodium polycarboxylate, which makes the pigment and filler more uniformly dispersed in the paint, adheres to the surface of the pigment and filler, reduces the surface tension of the pigment and filler, and prevents the pigment and filler from agglomerating and affecting the performance of the paint; the leveling agent is an organic silicon leveling agent; and the defoaming agent is a polyether-modified organic silicon defoaming agent.
[0076] The specific preparation process of the low-gloss and low-reflectivity paint special for aluminum coils is as follows:
[0077] The above-mentioned components of the paint are added to a stirring tank in proportion, and stirring is continuously carried out at a stirring speed of 1000 rpm or more for 2 h to obtain the low-gloss and low-reflectivity paint special for aluminum coils.
[0078] The prepared paint is coated on the surface of an aluminum coil product, and a film is formed after ultraviolet light curing, with a film thickness of 2-5 μm; the length of the light curing channel for the coated aluminum coil is 50 m, and the coating speed is 60 m / min.
[0079] Example 3
[0080] A low-gloss and low-reflectivity paint special for aluminum coils comprises the following components in parts by weight:
[0081] Polyurethane acrylate dispersion 85 parts, photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propyl ketone 4.2 parts, pigment and filler 30 parts, auxiliary agent 10 parts, and solvent 30 parts.
[0082] The polyurethane acrylate dispersion is the same as in Example 1.
[0083] The pigment and filler is the composite of silicon-titanium oxide loaded with carbon black prepared in Preparation Example 2, and the flatting agent is fumed silica, and the mass ratio of the two is 35:10.
[0084] The solvent is xylene and butyl acetate, and the mass ratio of the two is 10:45.
[0085] The auxiliary agent is dispersant 2.5 parts by weight, defoaming agent 4 parts by weight, and leveling agent 1.5 parts by weight; the dispersant is sodium polycarboxylate, which makes the pigment and filler more uniformly dispersed in the paint, adheres to the surface of the pigment and filler, reduces the surface tension of the pigment and filler, and prevents the pigment and filler from agglomerating and affecting the performance of the paint; the leveling agent is an organic silicon leveling agent; and the defoaming agent is a polyether-modified organic silicon defoaming agent.
[0086] The specific preparation process of the low-gloss and low-reflectivity paint special for aluminum coils is as follows:
[0087] The paint components were added into a stirring tank in proportion, and stirred at a speed of 1000 rpm for 1 h to obtain a low gloss and low reflectivity paint for aluminum coil after mixing evenly.
[0088] The prepared paint was coated on the surface of aluminum coil products, and a film was formed after UV curing, with a film thickness of 2-5 μm; the coating aluminum coil UV curing channel length was 50 m, and the coating speed was 80 m / min.
[0089] Comparative Example 1
[0090] The preparation process of the paint of the present case was the same as that of Example 1, except that the color filler in the composition of the paint was only the flatting agent.
[0091] Comparative Example 2
[0092] The preparation process of the paint of the present case was the same as that of Example 1, except that the color filler in the composition of the paint was titanium dioxide, carbon black, mica powder and flatting agent (the amount was consistent with Example 1, and no composite was formed).
[0093] The paints prepared in the above examples and comparative examples were respectively coated on the surface of aluminum coils with the same mass and thickness, and cured to form a film, and the prepared aluminum base was tested for gloss and reflectivity.
[0094] Gloss test: tested according to the standard of ASTM D532-2009 using a gloss meter, and the test angle was 60 degrees; the visible light and near-infrared light reflectivity of the coating was tested using a BenQ spectrophotometer, and the results are shown in Table 1.
[0095] Table 1 Performance of paint of each case
[0096]
[0097] As can be seen from Table 1, Comparative Example 1 and Example 3 were compared, and the gloss and reflectivity of the coating formed on the surface of the aluminum coil of the paint of Example 3 were lower; Example 3, Example 1 and Example 2 were compared, and the gloss and reflectivity of the coating formed on the surface of the aluminum coil of Example 1 and Example 2 were similar to those of Example 3, but the whiteness of Example 1 was higher than that of Example 2, indicating that the color fillers added in Example 1 and Example 2 had an effect, which could effectively reduce the gloss and reflectivity of the paint and improve the whiteness of the aluminum coil.
[0098] As can be seen from the above, the preparation of the paint of Example 1 was better, and the gloss and reflectivity of the surface of the aluminum coil after roll coating were significantly lower than those of other examples, and the effect of reducing the gloss and reflectivity of the aluminum coil was better.
[0099] The above merely describes preferred specific embodiments of the present application, but the protection scope of the present application is not limited thereto, and any person skilled in the art, according to the technical solution and inventive concept of the present application, makes equivalent replacement or change within the technical range disclosed by the present application, which should be covered within the protection scope of the present application.
Claims
1. A low-gloss, low-reflectance coating specific to aluminum coils, characterized in that, Comprise the following components by weight: Polyurethane acrylate dispersion 60-90 parts, photoinitiator 2-5 parts, pigment and filler 20-30 parts, auxiliary 6-10 parts, solvent 18-35 parts; The polyurethane acrylate dispersion is prepared by the following preparation method: (1) Under nitrogen protection, toluene diisocyanate and hydroxypropyl methacrylate are added into a reactor and mixed uniformly, and then reacted at 70-80℃ for 2-3h; (2) Carboxyl type chain extender is added and the reaction temperature of step (1) is maintained for chain extension reaction for 1-3h; (3) Then, the reaction temperature is lowered to 55-65℃, and polymerization inhibitor and catalyst are added for reaction for 3-5h; (4) Then, basic amine substance is added to adjust the pH value to 7-9, to obtain polyurethane acrylate prepolymer, and emulsification to obtain polyurethane acrylate dispersion; The pigment and filler is selected from one or more combinations of matting agent, silicon-titanium oxide loaded titanium dioxide and / or carbon black composite, and silica loaded mica powder composite.
2. A low gloss, low reflectance coating for aluminum coils as defined in claim 1, characterized in that, In step (1), the molar ratio of hydroxypropyl methacrylate to toluene diisocyanate is 1:0.8-1.2; In step (2), the carboxyl type chain extender is one or more than two mixtures of dimethylol propanoic acid and dimethylol butyric acid, and the mass ratio of the amount of carboxyl type chain extender to toluene diisocyanate is 0.6-1:1; In step (3), the polymerization inhibitor is p-hydroxyanisole, and the catalyst is dibutyltin dilaurate, and the molar ratio of the polymerization inhibitor, the catalyst, the hydroxypropyl methacrylate and the toluene diisocyanate is 0.001-0.1:0.075-0.2:1-1.2:0.9-1.1; In step (4), the emulsification process is: adding an emulsifier to the polyurethane acrylate prepolymer, stirring at a speed of 800-1000rpm for 0.5-2h, adding ethanol in multiple batches, and uniformly dispersing to obtain the product; the emulsifier is selected from any one of TX-10 and T-80; the mass ratio of the emulsifier, the polyurethane acrylate prepolymer and ethanol is 5-10:85-100:70-110.
3. A low gloss, low reflectance coating for aluminum coils as defined in claim 2, characterized in that, The pigment and filler is selected from one or more combinations of matting agent, silicon-titanium oxide loaded titanium dioxide and / or carbon black composite, and silica loaded mica powder composite, and the mass ratio of the matting agent, silicon-titanium oxide loaded titanium dioxide and / or carbon black composite, and silica loaded mica powder composite is 8-10:35-50:45-50; The delustering agent is selected from fumed silica having a specific surface area of 350-410 m 2 / g, a particle size of 200-500 mesh; the titanium white in the complex of titanium white and / or carbon black supported by the silicate-titanium oxide is rutile titanium dioxide having a particle size of 10-50 nm, and the carbon black has a particle size of 100-200 nm.
4. A low gloss, low reflectance coating for aluminum coils as defined in claim 3, characterized in that, The method for obtaining the silicon-titanium oxide loaded titanium dioxide and / or carbon black composite is: adding tetrabutyl titanate and tetraethyl orthosilicate to a dispersion liquid containing titanium dioxide and / or carbon black, adjusting the pH value of the reaction system to be acidic for reaction, washing the reaction liquid with anhydrous ethanol multiple times after the reaction is completed, drying the product after being separated, and finally calcining to obtain the silicon-titanium oxide loaded titanium dioxide and / or carbon black composite; The pH value is 2-5, the reaction temperature is 30-70℃, the reaction time is 0.5-24h, the calcination temperature is 400-600℃, and the calcination time is 3-8h. When titanium dioxide or carbon black is selected, the weight ratio of titanium dioxide or carbon black, tetrabutyl titanate and tetraethyl orthosilicate is 1:0.03-0.05:0.15-0.35; When titanium dioxide and carbon black are selected in combination, the weight ratio of titanium dioxide and carbon black is 1:0.2, and the weight ratio of the total amount of titanium dioxide and carbon black to tetrabutyl titanate and tetraethyl orthosilicate is 1.2:0.032-0.06:0.18-0.
45.
5. A low gloss, low reflectance coating for aluminum coils as defined in claim 3 wherein, The method for obtaining the silica-loaded mica powder composite is: mixing silica powder with a particle size of 1-100 nm and mica powder with a flake size of 1-250 nm under the action of a silane coupling agent by ball milling to obtain a silica-loaded mica powder composite; wherein the mass ratio of the silica powder, the mica powder and the silane coupling agent is 1:0.5-1:0.1-0.3; the ball milling uses zirconium oxide beads with a particle size of 0.6-1 mm as grinding media to continuously grind the materials for 1-3 h.
6. A low gloss, low reflectance coating for aluminum coils according to any one of claims 1-5, characterized in that, The photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propyl ketone; The solvent is a mixed solvent of xylene and butyl acetate in a weight ratio of 10:45-60; The auxiliary agent is selected from one or more of a leveling agent, a dispersing agent and a defoaming agent; The leveling agent is a silicone leveling agent, and the amount of the leveling agent added in the coating component is 0.5-2 parts by weight; The dispersing agent is a polycarboxylic acid sodium salt dispersing agent, and the amount of the dispersing agent added in the coating component is 1-3 parts by weight; The defoaming agent is a polyether-modified silicone defoaming agent, and the amount of the defoaming agent added in the coating component is 3-5 parts by weight.
7. A method for producing a low-gloss, low-reflectance coating specific to aluminum coils, characterized by, The method comprises the following steps: The low-gloss and low-reflectivity paint according to any one of claims 1-6 is prepared by mixing the components in a stirring tank at a stirring speed of 1000 rpm or higher for 0.5-2 h, and then uniformly mixing.
8. The method of claim 7, wherein the low-gloss, low-reflectance coating for aluminum coils is prepared by the steps of: The low-gloss and low-reflectivity paint is coated on the surface of an aluminum rolled product, and a film is formed after ultraviolet curing, with a film thickness of 2-5 μm, an ultraviolet curing channel length of 50 m and a coating speed of 50-80 m / min.
Citation Information
Patent Citations
Heat-insulation heat-preservation powdered paint, preparation method and coating method of heat-insulation heat-preservation powdered paint, coating formed by using coating method and application of coating
CN104449200A